Effect of Teak Wood Dust as Filler Material on Mechanical Properties of Abaca-Pineapple-Epoxy Hybrid Composite - Maruthi Prashanth B H; Sandeepkumar Gowda; Ramesh S; Nagaraja T K; Zaheerabbas B Kandagal; Prashanth Pai M; Divijesh Puninchathaya P; Priyaranjan Sharma; Gajanan Anne (Journal of Natural Fibers)
Composite manufacturers and consumers are increasingly turning to natural-based composites for their biocompatibility, cost-effectiveness, and widespread availability. This study investigates the potential of using teak wood dust as an economical filler material, combined with natural fibers, within an epoxy matrix to create a composite. Specifically, it examines how varying concentrations of teak wood dust—3 wt%, 6 wt%, and 9 wt%—affect the mechanical properties such as tensile strength, flexural strength, impact resistance, inter-laminar shear strength (ILSS), and hardness of an abaca-pineapple-epoxy hybrid composite. The composites were fabricated using the hand layup method followed by hot pressing. Among the different configurations, the composite with 6 wt% teak wood dust (SD-6) demonstrated superior performance, with improvements in tensile, flexural, ILSS, and impact strengths ranging from 3% to 35% compared to other variants. Scanning Electron Microscope (SEM) analysis of the fractured surfaces indicated that the inclusion of 6 wt% teak wood dust enhanced fiber-matrix adhesion, leading to improved mechanical properties of the composite.